TAB-TICI Score: Successful Recanalization Score After Endovascular Thrombectomy in Acute Stroke - Seo, Woo-Keun; Nam, Hyo Suk; Chung, Jong-Won; Kim, Young Dae; Kim, Keon-Ha; Bang, Oh Young; Kim, Byung Moon; Kim, Gyeung-Moon; Jeon, Pyoung; Heo, Ji Hoe (Frontiers in Neurology, 2021)
Background and Purpose—This study aimed to develop a novel scoring system for defining the successful recanalization after endovascular thrombectomy. Methods—We analyzed the data of consecutive acute stroke patients who were eligible to undergo reperfusion therapy within 24 h of onset and who underwent mechanical thrombectomy using a nationwide multicenter stroke registry. New score was produced using the predictors which were directly linked to procedure to evaluate the performance of thrombectomy procedure. Results—In total, 446 patients in the training population and 222 patients in the validation population were analyzed. From the potential components of the score, four items were selected: ER-to-puncture time (T), adjuvant devices used (A), procedural intracranial bleeding (B), and post-thrombectomy reperfusion status [Thrombolysis in Cerebral Infarction (TICI)]. Using these items, the TAB-TICI score was developed, which showed good performance in terms of discriminating early neurological aggravation [AUC 0.73, 95% confidence interval (CI) 0.67–0.78, P<0.01] and favorable outcomes (AUC 0.69, 95% CI 0.64–0.75, P<0.01) in the training population. Stability of the TAB-TICI score was confirmed by external validation and sensitivity analyses. The TAB-TICI score and its derived grade of successful recanalization were significantly associated with the volume of thrombectomy cases at each site and in each admission year. Conclusion—The TAB-TICI score is a valid and easy-to-use tool for the successful recanalization after endovascular thrombectomy in acute stroke patients with LVO.